COMPASSION AMIDST REJECTION: AN ISLAMIC PSYCHOLOGICAL ANALYSIS OF THE RELATIONSHIP BETWEEN PROPHET NOAH AND HIS SON IN SURAH HUD [11]: 42–43 - Marwa; Mahda; Desi Erawati (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
The story of Prophet Nuh and his son in QS. Hūd [11]: 42–43 presents a profound depiction of parent-child relations within the context of differing faith. Beyond its historical dimension, this narrative serves as a spiritual reflection of how love, authority, and freedom of choice intersect within family education. This study aims to analyze the relationship between Prophet Nuh and his son from the perspective of Islamic psychology, to reveal educational values applicable to contemporary family settings. This research employs a qualitative-descriptive method using a thematic tafsir approach combined with Islamic psychological analysis, examining Qur’anic text and relevant literature. The findings indicate that the son's rejection was not merely an emotional conflict but a form of spiritual disobedience rooted in al-qalb al-mughlaq (a closed heart). In contrast, Nuh’s response reflects exemplary patience, trust in God (tawakkul), and rahmah-based education, prioritizing empathy and moral example over coercion. The study concludes that guidance (hidayah) cannot be forced, and that the primary role of parents in Islam is to lovingly convey the truth while entrusting the outcome to Allah SWT.